Ammunition Scheduling Method in Airborne Weapon Depot Based on Improved Genetic Algorithm - Liu, Min; Li, Guanfeng (Journal of physics. Conference series, 2021)
The scheduling of the carrier-based aircraft weapon involves many resources and is subject to many constraints. The design of the scheduling scheme belongs to a type of typical NP-Hard problem. In this paper, genetic algorithm is selected as the optimization algorithm, and a two-layer real-value coding method is designed, and the selection, cross, and mutation operations of the algorithm are improved by using the elite strategy and other methods. The improved algorithm was used to simulate the established mathematical model to verify the effectiveness and superiority of the improved algorithm.